2009
DOI: 10.1111/j.1547-5069.2009.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Work Interruptions During Medication Administration

Abstract: Interventions to reduce WIs during the medication administration process should target nurses and system failures to maximize medication administration safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
3
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 23 publications
8
104
3
9
Order By: Relevance
“…These interruptions are significant because of adverse events noted in the literature regarding the adverse effects of interruptions on efficiency and error. [11][12][13][14] Task reacquisition times within this context have had limited prior exploration in one study, 1 which utilized dedicated observers. Our study examined behaviors among existing members of the clinical team and was not resourced to capture these data.…”
Section: Discussionmentioning
confidence: 99%
“…These interruptions are significant because of adverse events noted in the literature regarding the adverse effects of interruptions on efficiency and error. [11][12][13][14] Task reacquisition times within this context have had limited prior exploration in one study, 1 which utilized dedicated observers. Our study examined behaviors among existing members of the clinical team and was not resourced to capture these data.…”
Section: Discussionmentioning
confidence: 99%
“…Manually collected data were entered into a database (MS Access, Microsoft, Seattle, Washington) and were analyzed using SPSS 15.0 (IBM, Armonk, New Mean hourly rates of stimuli observed in this study were higher than those reported in similar studies in other health care settings. 1,[8][9][10][11][12][13] In one study of pharmacy practice, pharmacists and pharmacy technicians were exposed to 6 interruptions per hour, while physicians and nurses were each exposed to 4 to 10 interruptions per hour. 1 An analysis of 4 stimuli related to the corrective measures implemented in 2011 highlighted significant reductions in certain stimuli for certain groups of pharmacy professionals.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] The work environment is error-prone, especially during complex or high-risk activities, because interruptions and multitasking behaviors create conditions affecting working memory and attention resources. 9,10 Nurses' cognitive processes during medication administration are complex and require a high degree of critical thinking and vigilance to prevent patient harm.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…8,12 System failures such as missing medications and access to equipment and supplies were also identified as sources of interruptions that are potentially avoidable. 7,8,[12][13][14][15][16] Other avoidable interruptions cited in the literature are the tendency of nurses to interrupt each other with conversations unrelated to medication administration 7,[17][18][19] while preparing medications and to respond immediately to requests from others when interrupted. 7,15,20 These findings support the idea that interruptions are an accepted part of nursing practice and suggest the Attendance at the National Teaching Institute was the inspiration for this project and the springboard for addressing existing nursing concerns about interruptions.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation